The first genetically confirmed live sighting of the Deraniyagala's beaked whale ( Mesoplodon hotaula ), with insights into the diversity, phylogeny, and past demographic history - Wenzhi Lin; Hui Kang; Inge Seim; Binshuai Liu; Shenglan Chen; Mingming Liu; Lijun Dong; Mingli Lin; Yuhang Song; Mingyue Ouyang; Xiaoyu Huang; Yingxue Gao; et al. (Marine Mammal Science, 2025)
Beaked whales have recently been reported in the South China Sea but with taxonomic uncertainty due to their ambiguous morphological features. Here, we sequenced three genetic markers, the control region (CR) and cytochrome b ( cytb ) of the mitochondrial genome and the first intron of the nuclear muscle actin gene ACTA2 , of two biopsy samples collected in 2021, and revealed unambiguous clustering with sequences previously attributed to Deraniyagala's beaked whale ( Mesoplodon hotaula ). Phylogenetic analysis of complete mitogenomes strongly supported the close relationship between the Deraniyagala's beaked whale and the ginkgo‐toothed beaked whale ( M. ginkgodens ). Whole‐genome sequencing suggested a high degree of heterozygosity in the Deraniyagala's beaked whale. Ancient inbreeding may have had a greater impact than the recent inbreeding on Deraniyagala's beaked whales, but more samples are needed to draw a firm conclusion. The approximate effective population size of Deraniyagala's beaked whale was found lowest among seven examined ziphiids, which has been experiencing a steady decline since ~300,000 ya. Therefore, we suggest that the conservation status of Deraniyagala's beaked whales should be assessed when essential information is available. The results of our study provide genetic evidence of the live sighting of Deraniyagala's beaked whale in the South China Sea and are fundamental to understanding the morphological, behavioral, and ecological perspectives of this cetacean species.